GAMBARAN BEBAN KERJA MENTAL PADA PEKERJA UNIT AVIATION SECURITY - Aracelly Putri Pribadi; Noeroel Widajati (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
The decrease in the number of human resources in the aviation security unit at one airport allows for an increase in workload, especially mental workload, because when on duty, aviation security unit workers require high accuracy and concentration. The purpose of this study was to determine the level of mental workload on aviation security unit workers at one airport. This research is included in descriptive research with a cross sectional approach. The target of this study was 251 aviation security unit workers at one airport. From the population, a sampling technique was carried out using the simple random sampling method with the sloving method, so that the number of respondents was 72 aviation security unit workers at one airport. The techniques and procedures for data collection were using the NASA-TLX questionnaire and individual characteristics questionnaires related to age and gender. Descriptive data analysis technique was used to describe the collected data. Based on the results of the analysis, it is known that most of the respondents are male and the majority of the respondents are aged 26-35 years. Most of the respondents who filled out the questionnaire were married and had education status at the high school level. The results showed that most of the respondents were included in the high mental workload group, namely 38 respondents. This shows that the mental workload obtained by most workers is a mental workload with a high category so that control measures need to be taken to avoid the negative impact of the high mental workload